The nutritive value and use of feeds for fattening small ruminants in African highlands: A perspective of ILCA's research - Reed, J.D.; Ebong, Cyprian; Tanner, J.C.; Gebru, G.; Akalework, N. (International Livestock Centre for Africa, 1988)
Presents and discusses ILCA's research approach on the development of sustainable feeding systems for increasing small ruminant production on smallholder farms. Examines in detail the three levels of interrelated research activities, viz, strategic research, commodity research and on-farm development.